Business cycle dependent unemployment insurance - Torben M. Andersen; Michael Svarer (Kiel Institute for the World Economy (IfW), 2009)
The consequences of cylical contingencies in unemployment insurance systems are considered in a search-matching model allowing for shifts between "good" and "bad" states of nature. An argument for state contingencies is that insurance arguments are stronger and incentive effects weaker in bad than in good states of nature. We con.rm this and show that cyclically dependent benefit levels not only provide better insurance but may have structural effects implying that the structural (average) unemployment rate decreases, although the variability of unemployment may increase.
Keywords: 330; Arbeitslosenversicherung; Konjunkturelle Arbeitslosigkeit; Arbeitsplatzsuchmodell; Theorie